Analisis Implementasi Program Makan Bergizi Gratis 2025: Studi Literatur Dilema Efektivitas dan Kualitas - Mulyani, Seri; Maifizar, Arfriani (Jurnal Sociohumaniora Kodepena (JSK), 2025)
The Free Nutritious Meal Program 2025 is a strategic government policy aimed at addressing nutritional problems and improving the quality of human resources from an early age. However, its implementation has generated social dilemmas related to the effectiveness of distribution and the quality of the food provided. This study aims to analyze the extent to which the program can achieve its social objectives without neglecting quality standards and sustainability. The research employs a descriptive qualitative method with data collected through a literature review of academic sources and relevant policy reports. The study applies Merilee S. Grindle’s policy implementation theory, which emphasizes two key aspects: Content of Policy and Context of Implementation. In this context, the dilemma arises when the policy content demands high nutritional standards and food quality, while the implementation context faces challenges such as geographical constraints, logistical limitations, and varying capacities of local vendors. The findings indicate that the program is effective in expanding access to nutritious food for vulnerable groups but still encounters obstacles in food quality, distribution timeliness, and budget transparency. The program’s effectiveness can only be achieved if implementation quality, accountability, and collaboration among stakeholders are consistently and sustainably strengthened.